EVALUATING AUDIT MARKET COMPETITION AND PRICING IN INDONESIA - Anggraita, Viska; Fitriany, Fitriany; Sinaga, Ramona; Kiantara, Rio Ferdinand (KEUNIS, 2024)
The purpose of this research is to examines how is the competition and pricing for audit services in the audit service market in Indonesia from the perspective of the auditors. This study uses a questionnaire with auditor respondents at manager level to audit partners. The data analysis technique used in this research is descriptive statistical analysis. By using a total of 414 respondents from audit firms Big 4 and non-Big 4, this research found that most of the respondents considered the audit service market competition in Indonesia to be high and agree that competition for audit services creates pressure that creates relatively low audit fee in Indonesia. The results of this study confirm and strengthen previous studies which using secondary data that the level of concentration of the audit services market is related to the level of competition for audit services and create pressure to reduce audit fee.   The implication of this research is that further research needs to be carried out using more objective secondary data to examine the impact of the level of competition of audit services on audit fees and audit quality as well as evaluating whether regulations are needed to determine minimum  audit  fees.